From vaccine hesitancy to vaccine motivation: A motivational interviewing based approach to vaccine counselling - Arnaud Gagneur; Damara Gutnick; Patrick Berthiaume; Alessandro Diana; Stephen Rollnick; Prantik Saha (Human Vaccines & Immunotherapeutics)
The COVID-19 pandemic highlighted Vaccine Hesitancy (VH) as an accelerating global phenomenon that must be addressed. According to the WHO, thirty to fifty percent of the world’s population are VH. Motivational Interviewing (MI) is an evidence-based communication style demonstrated to significantly reduce VH. MI guides people toward change through the expression of empathy and by respecting an individual’s autonomy. Healthcare providers (HCPs) are the primary implementors of vaccine policies and the most trusted advisors and influencers of vaccination intention at the individual patient level. Training HCPs in MI is one of the most effective strategies to overcome VH. Many countries are currently implementing HCP training programs and population-based MI interventions to improve vaccine uptake. MI conversations are ‘the heart’ of vaccine decision-making processes. Understanding individual patient-level drivers of hesitancy allows clinicians to efficiently provide tailored, accurate information that reinforces a person’s own motivation and confidence in their own decision. This paper describes a 4-step practical framework designed to support HCPs in their dialogue with vaccine-hesitant patients. (1) Engaging to establish a trustful relationship and safety to freely express opinions, beliefs, and knowledge gaps; (2) Understanding what matters most to the individual; (3) Offering Information to co-build accurate knowledge in order to guide the individual toward vaccine intention (4) Clarifying and Accepting to validate an individual’s decision-making autonomy. We believe that our pragmatic approach can contribute to greater acceptability of COVID-19 and other vaccines, and enable rapid deployment of practical MI skills across care systems.